THE EFFECTIVENESS OF EXERCISE SPIN SERVE MODEL ON LAWN TENNIS BASED KINOVEA - Ians Aprilo; Moch. Asmawi; James Tangkudung (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2021)
The purpose this article is explain about influence the exercise spin serve on lawn tennis model based kinovea. The article will expose result of research in an effort to improved spin serve skills on lawn tennis. Method the research is experiment pretest - posttest control group design. The participant is 60 college student which can played lawn tennis with average abilities. The participant divided two group, the treatment and control group, 30 participants each. The research was conducted on sport science faculty state University of Makassar for two months. Implementation of treatment thrice e weeks and total 18 meetings. Data analysis have used parametric statistic. Researchers have tested data normality, homogeneity, as well independent and paired test, have used computer with SPSS program. The results of study have shown that there have been significant differences before and after exercise using spin serve model based of kinovea. Statistical result obtained by the t value of 3.08, the average value of -8.60m degree of freedom = 29, and sig. 0.000 (P<0.05). There has also been a significant difference between the treatment and control groups, it is obtained the statistical t value of 13.36, degree of freedom=58, and the sig. 0.000 (P<0.05).